Tourism-Led Local Economic Development: Assessing the Employment Creation of Lowokdoro Bird Contest Tourism - Suliswanto, Muhammad Sri Wahyudi; Firmansyah, Muhammad; Jifatu, Ibrahim Halilu (Badan Perencanaan Pembangunan Kota Malang, 2026)
The creation of tourism-based employment is a key policy issue for local governments seeking to develop tourism as a driver of inclusive and sustainable job creation. This study analyzes the role of Gantangan Burung Lowokdoro Tourism in Malang City in creating employment and generating local economic linkages through event tourism activities. Using a qualitative descriptive case study design, data were collected through field observations and documentation. Data were analyzed by classifying economic activities, identifying direct and indirect labor involvement, and mapping job creation patterns across event operations, MSMEs, and supporting services. SWOT analysis was used to assess governance and institutional factors affecting employment sustainability and destination management strategies. The findings indicate that event-based tourism contributes to local job creation. Direct employment includes committee members, judges, and technical staff, while indirect employment involves local business actors, including MSMEs, food vendors, parking attendants, and local transportation providers. These findings demonstrate that indirect employment depends on the integration of local economic actors within the tourism ecosystem. The employment pattern is hybrid, combining temporary event-based jobs with semi-permanent economic activities that develop alongside event sustainability. Tourism activities also support business opportunities in hospitality, trade, transportation, and other supporting services, strengthening local economic linkages. However, employment sustainability depends on event continuity and governance, including stakeholder coordination, management capacity, partnerships, supporting facilities, and institutional strengthening. Theoretically, this study contributes to event tourism and development economics by explaining community-based employment creation through local economic linkages. Policy implications emphasize strengthening institutional capacity, MSME participation, and stakeholder collaboration to support sustainable tourism-based employment.